Проектирование нефтяных и газовых скважин / ДО 2015: электронный курс - Ковалев А. В. Артем Владимирович; Башкиров И. А. Иван Александрович; Молоков В. Ю. Виктор Юрьевич; Глотова В. Н. Валентина Николаевна (Томск, TPU Moodle, 2020)
Заглавие с экрана